Flow by redistribution of water through profiles of the unsaturated zone under conditions of agricultural land use in the Páez upper watershed, Cartago, Costa Rica - Ramírez-Granados, Pablo; Villagra-Mendoza, Karolina; Masís-Meléndez, Federico (Revista Geográfica de América Central., 2022)
The main objective of this study was to analyze the flow of water by redistribution through the horizons of volcanic soil profiles in the unsaturated zone once the infiltration of rainwater has been completed. From experimental monoliths, volumetric water contents were monitored in profiles at different depths to understand the temporal flow dynamics along a profile. The physical and hydraulic properties of the horizons such as texture, granulometry, organic matter, bulk density, real density, were evaluated in the laboratory, porosity, hydraulic conductivity, and moisture retention. It was found that the physical and hydraulic properties of the horizons help to explain the behavior of the water in depth. Water contributions by depth redistribution, due to vertical flow, were found from the analysis of volumetric water contents. These contributions are evidenced by increases in volumetric contents during the development of the experiment. From the experimental study it was possible to observe how the flow by redistribution varies in the profiles of a horizon, thus showing the variation of the properties of the horizons in depth. Once water redistribution flows were established, the types of water flow manifested in the monolith profiles were characterized to establish what the dynamics of the deep wetting front are and how it advances during the development of the experiment. The results showed that in the monoliths the piston flow, the preference flow and the dual or combined flow product of the combination of both are presented.